MACROECONOMIC ASPECTS AND CHALLENGES IN ROMANIA IN THE FIRST HALF OF 2016 - BARBU, Cristian Marian (Annales Universitatis Apulensis Series Oeconomica, 2016)
This paper reveals that fact that although Romania had a significant economic growth during the first half of 2016 (5,2%), and it was the European economy with the highest growth rate, the consolidated general budget had a deficit of 3.12 billion lei after the first 8 months of 2016, equal to 0.41%  of the GDP estimated for 2016. The result is 10 billion lei below the same period of 2015, due to a mix of policies that resulted into stimulated demand and fiscal relaxation. The paper also analyses the foreign investments in 2015, per country of origin of investments, development regions and sectors of activity. Romania holds the 62nd place among most competitive 138 countries in the world, according to the WEF 2016 – 2017 report published in September 2016, and a set of problematic factors show that Romania does not have currently the necessary ingredients to leap from a middle economy to a developed economy, and it looks like caught in the „middle income trap”.